EURECA: On-chip configuration generation for effective dynamic data access - Niu,X; Luk,W; Wang,Y (2015)
This paper describes Effective Utilities for Run-timE Configuration Adaptation (EURECA), a novel memory architecture for supporting effective dynamic data access in reconfigurable devices. EURECA exploits on-chip configuration generation to reconfigure active connections in such devices cycle by cycle. When integrated into a baseline architecture based on the Virtex-6 SX475T, the EURECA memory architecture introduces small area, delay and power overhead. Three benchmark applications are developed with the proposed architecture targeting social networking (Memcached), scientific computing (sparse matrix-vector multiplication), and in-memory database (large-scale sorting). Compared with conventional static designs, up to 14.9 times reduction in area, 2.2 times reduction in critical-path delay, and 32.1 times reduction in area-delay product are achieved.